2018
DOI: 10.1097/j.pain.0000000000001226
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain impairs cognitive flexibility and engages novel learning strategies in rats

Abstract: Cognitive flexibility, the ability to adapt behavior to changing outcomes, is critical to survival. The prefrontal cortex is a key site of cognitive control, and chronic pain is known to lead to significant morphological changes to this brain region. Nevertheless, the effects of chronic pain on cognitive flexibility and learning remain uncertain. We used an instrumental paradigm to assess adaptive learning in an experimental model of chronic pain induced by tight ligation of the spinal nerves L5/6 (spinal nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…In the present study, MIA treatment did not impair operant performance and operant measures of behavioural flexibility, including rule shifting and reversal learning. Previous studies in rat models of neuropathic pain reported impaired operant performance, including slower adaptation to optimal choices [15], and impaired spatial reversal learning in the watermaze [31]. These measures do appear to have translational relevance as chronic pain patients with fibromyalgia and primary Sjögren syndrome with small fibre neuropathy show impaired behavioural flexibility on the Wisconsin Card Sorting Test [22,63].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, MIA treatment did not impair operant performance and operant measures of behavioural flexibility, including rule shifting and reversal learning. Previous studies in rat models of neuropathic pain reported impaired operant performance, including slower adaptation to optimal choices [15], and impaired spatial reversal learning in the watermaze [31]. These measures do appear to have translational relevance as chronic pain patients with fibromyalgia and primary Sjögren syndrome with small fibre neuropathy show impaired behavioural flexibility on the Wisconsin Card Sorting Test [22,63].…”
Section: Discussionmentioning
confidence: 99%
“…In the SNI model of neuropathy, chronic pain reduces the overall amount of information flowing in the fronto-hippocampal circuit [ 324 ]. Chronic pain also impairs cognitive flexibility and engages novel learning strategies in rats [ 325 ]. Surgical incision-induced nociception reduces the level of synaptic NMDA receptor 2B in the mPFC of mice, and this reduction has been suggested to contribute to a loss of cognition [ 326 ].…”
Section: Links Between Pain and Depression Anxiety And Cognition Anmentioning
confidence: 99%
“…Substantial evidence suggests the detrimental effect of chronic pain on cognition (Cowen et al, 2018;Matthewson et al, 2019;Phelps et al, 2021). Nonetheless, whether cognitively compromised animals with pain have the exact same synaptic mechanisms as those in the cognitively normal animals with pain remains to be elucidated so far.…”
Section: Discussionmentioning
confidence: 99%